Soc 274- Social Statistics - Brashears, Matthew E. (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
The primary objective of this course is to introduce students to the concepts of statistical analysis. Statistics are a way to describe the world, much like a language, and this course is intended to teach you how to speak that language, and understand it when it is spoken to you. Statistics are used in everything from advertisements, to political speeches, to sports. An understanding of statistics is, therefore, essential to being a literate, empowered, adult. Beyond that, statistics allow us to see the world with more than simply our own eyes. Statistics can allow us to pluck certainty from the vapor of possibility, providing insight we couldn’t get anywhere else. While completion of prerequisites with the math department is necessary for this course, this is not a math class in the traditional sense. This class focuses on teaching you to use mathematics to answer substantive questions, and on learning how to interpret what the math is telling you. By the end of class students should have an understanding of what statistics are, the limitations of statistical analysis, possess the skills to interpret statistics, and be capable of conducting certain types of analyses themselves.